KEMANDIRIAN ANAK USIA 5-6 TAHUN DI KOMUNITAS LINGKUNGAN PEMULUNG - Siti Rahma, Ade Dwi Utami, Hapidin (Jurnal Ilmiah Visi, 2016)
The research aims at obtaining information and empirical data of independence of 5 -6 years old children in the community of garbage collectors TPST Sumur Batu, Bantar Gebang, Bekasi. Using qualitative method, the research was conducted in May and June 2015. The data was collected by observation, interview and document study to analyzed employing Miles and Huberman technique. Data was verified by prolonging observation and triangulation. Research findings showed that self-reliance of 5-6 years old children in the garbage collector community is built by the role and attitude of their parents and the environment. The research conclusion indicates independent children are not built by themselves. The parents should assist the children as early as possible to enable them to do their activities without depend themselves on their parents.